Does membership on the UN Security Council influence IMF decisions? Evidence from panel data - Axel Dreher; Jan-Egbert Sturm; James Raymond Vreeland (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
We investigate whether temporary members of the UN Security Council receive favorable treatment from the IMF, using panel data for 191 countries over the period 1951 to 2004. Our results indicate a robust positive relationship between temporary UN Security Council membership and participation in IMF programs, even after accounting for economic and political factors, as well as regional and country effects, and duration dependence. There is also evidence that UNSC membership reduces the number of conditions included in IMF programs. The size of the loan, however, is not affected by UNSC membership.
Keywords: F33; 330; IMF; UN Security Council; Voting; Aid